Public Budgeting in America. - Stolp, Chandler; Lynch, Thomas D. (Journal of Finance, 1981)
(NOTE: Section Ends with Review Questions and References.) 1. Public Budget in Context. 2. Toward Modern Budgeting. 3. Budget Behavior. 4. Budget Formats and Preparation. 5. Analysis Applied to Budgeting. 6. Analytical Processes. 7. Operating Budgets and Accounting. 8. Capital Budgeting and Debt Administration. 9. Revenue Systems. 10. Internal Service Functions. Glossary. Index.